Improving the Ability to Read and Write Al-Qur’an Using the Iqra Method - Rifdah Fadilatul Munawaroh; Dian Rahmawati; Safarotunnajah Safarotunnajah; Dean Dwi Putra Putra; Imam Tabroni; Mahon Nitin (Journal Emerging Technologies in Education, 2023)
Background. This article aims to discuss the ability to read and write the Qur'an in grade 5 SDIT Kharisma Darussalam. Purpose. this research uses a descriptive correlational analysis research method namely research conducted to obtain a description of a reality. Method. The results of this study state that reading the Qur'an must be in accordance with good and correct rules by continuing to be trained by reading and writing. Results. In learning the Qur'an, it is necessary to know the hijaiyah letters and also how to write them as in the iqra method from hijaiyah letters to short verses in the Qur'an. Conclusion. Because understanding reading and writing the Qur'an is important for every Muslim as a guide in his life.